The Role of Employee Well-Being and Work-Life Balance in Driving Adaptive Performance in Manufacturing Companies - Mita Sri Kusuma; Muhamad Sapruwan (Lentera Ilmu Nusantara, 2026)
This study aims to analyze the effect of Employee Well-Being and Work–Life Balance to Adaptive Performance manufacturing company employees. The dynamic changes in the work environment require manufacturing employees to possess high adaptive performance. Psychological well-being and work–life balance are considered important factors in supporting employees' adaptability. This study aims to examine the effect of employee well-being and work–life balance on adaptive performance among manufacturing employees in the Bekasi area. This study employs a quantitative approach using a survey method through an online questionnaire. Convenience sampling was applied, resulting in 65 respondents. Data analysis is planned to be conducted using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The findings of this study are expected to contribute theoretically to organizational behavior literature and practically to manufacturing companies in improving employees' adaptive performance.